Civil War, Crop Failure, and Child Stunting in Rwanda - Akresh, Richard (World Bank, Washington, DC, 2012)
Economic shocks at birth have lasting effects on children's health several years after the shock. The authors calculate height for age z-scores for children under age five using data from a Rwandan nationally representative household survey conducted in 1992. They exploit district and time variation in crop failure and civil conflict to measure the impact of exogenous shocks that children experience at birth on their height several years later. They find that boys and girls born after the shock in regions experiencing civil conflict are both negatively affected with height for age z-scores 0.30 and 0.72 standard deviations lower, respectively. Conversely, only girls are negatively affected by crop failure, with these girls exhibiting 0.41 standard deviation lower height for age z-scores and the impact is worse for girls in poor households. Results are robust to using sibling difference estimators, household level production, and rainfall shocks as alternative measures of crop failure.